DINAMIKA AKTIVITAS BERDAGANG PAKAIAN BEKAS IMPOR (THRIFT) DI PASAR SENAPELAN KOTA PEKANBARU - Putri, Aprilia Purnama; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to comprehend the dynamics of trading activities of used imported clothing (thrift) in Senapelan Market, Pekanbaru City. To analyze the existing phenomenon, the researcher employs Max Weber's theory of rational action. This study employs a qualitative method utilizing data collection techniques through observation, interviews, and documentation. Subject selection is based on specific criteria, involving a total of 3 individuals as informants, comprising traders of used imported clothing, and 1 key informant, namely the Head of the Trade Division of the Pekanbaru City Industry and Trade Office. The research findings elaborate on the trading situation, activities, and relationships formed as factors that motivate and sustain the trade of used imported clothing in Pekanbaru city, despite government prohibitions. The presence of government regulations related to the ban on used imported clothing is not yet fully optimized in terms of implementation, thus requiring efforts and programs to be designed in order to enhance the enforcement of regulations to address the issues posed by used imported clothing, which brings significant impacts to Indonesia. Keywords: Used Clothing Import, Thrifting, Prohibition